Two new species and a new record of Begonia (Begoniaceae) from Vangvieng karst limestone in central Laos - Lanorsavanh, Soulivanh; Souvannakhoummane, Keooudone; Lamxay, Vichith; Chanthavongsa, Khamfa (Thai Forest Bulletin (Botany), 2021)
Begonia cataracta and B. voluptuaria are described as new species and B. incerta is noted as a new record for Laos. Descriptions, illustrations and photographs are provided for the new species and photographs for the new record. Preliminary conservation assessments are made for the two new species which are assessed as Vulnerable and Critically Endangered respectively.